A utilização da literatura de cordel como instrumento didáticometodológico no ensino de geografia. - Silva, Joseilton José de Araújo (2012)
This work has as main objective to analyze the possibilities of using Cordel as methodological-didactic instrument in the teaching of Geography. This literature, study object of this research, is presented as one of the richest expressions of popular culture. So being to be able to contextualize the teaching situations in the lessons of Geography and related disciplines. By bringing scientific knowledge of popular knowledge, the Cordel makes a bridge between academic knowledge and school knowledge. Geography presents to school, today, as a dynamic science and, therefore, bulit in space designed and lived. Assuming that poet of Cordel, here characterized as cordelista, expressed in its produccion characteristics of a knowledge bulit on cultural experiences and everyday, witch reveals the concepts of sociocultural reallity of particular place. The Northeast region, was defined as a spatial area of this research, as we seek to identify through a literature review and field research, the geographic content contained in these, they could effectively characterize this region in geography lessons. The character educational and informational contained in the cordeis can become a teaching resource and methodological able to facilitate the teaching-learning in basic education. This is already having is value recognized in higher education. However, with few exceptions, the basic education that is still largely untapped. To formulate the theoretical and methodological route of work that present, we try to show, the relationship between culture, popular and scientific knowledge, perspectives addressing the Critical an Cultural Geography and provoking a dialogue between the Academic and School Geographies. Seeking to highlight the potential of Cordel, we draw a historical and cultural panorama in Brazil and the Northeast of it. Making a correlation between it and informal education. Concluding our research process, we analyze some cordeis, trying to identify the character educational and the geographic contents about Northeast contained in these. We hope that this work can help future studies that aim to increase knowledge about the Cordel and its applicability as methodological-didactic instrument.